2021
DOI: 10.1186/s40623-020-01340-w
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductive fluid-rich zones and their influence on the earthquake initiation, growth, and arrest processes: observations from the 2016 Kumamoto earthquake sequence, Kyushu Island, Japan

Abstract: Crustal earthquake ruptures tend to initiate near fluid-rich zones. However, it is relatively unknown whether fluid-rich zones can further promote or arrest these ruptures. We image the electrical resistivity structure around the focal area of the 2016 Kumamoto earthquake sequence by using 200 sites broadband magnetotelluric data, and discuss its quantitative relationship to earthquake initiation, growth, and arrest processes. The ruptures that initiated along the outer edge of the low-resistivity fluid-rich z… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The fault-valve hypothesis of Sibson (1992) suggests that overpressured fluid reduces the frictional fault strength, inducing the earthquake and promoting upward fluid flow from deep fluid-rich reservoirs to the shallower crust, but the fluid pressure drop after the fault rupture subsequently reverses and rises once again. Recently, it is suggested that the overpressured fluids not only contribute to the initiation of earthquakes but also contribute to the final magnitude of earthquakes (Aizawa et al, 2021 barrier to upward fluid flow from fluid-rich domains with spherical or vertical elongated geometries, resulting in fluid stagnation below the brittle-ductile transition zone. They showed that the balance between the buoyancy forces acting on fluids and the vertical stress gradient in rocks causes such fluid stagnation zones.…”
Section: Discussionmentioning
confidence: 99%
“…The fault-valve hypothesis of Sibson (1992) suggests that overpressured fluid reduces the frictional fault strength, inducing the earthquake and promoting upward fluid flow from deep fluid-rich reservoirs to the shallower crust, but the fluid pressure drop after the fault rupture subsequently reverses and rises once again. Recently, it is suggested that the overpressured fluids not only contribute to the initiation of earthquakes but also contribute to the final magnitude of earthquakes (Aizawa et al, 2021 barrier to upward fluid flow from fluid-rich domains with spherical or vertical elongated geometries, resulting in fluid stagnation below the brittle-ductile transition zone. They showed that the balance between the buoyancy forces acting on fluids and the vertical stress gradient in rocks causes such fluid stagnation zones.…”
Section: Discussionmentioning
confidence: 99%
“…The first of these is the most likely candidate as previous studies of conductive anomalies in subduction zones (e.g., Aizawa et al 2021;Ichihara et al 2016;Evans et al 2014) and an experimental study for conductive antigorite (Reynard et al 2011) have suggested. The formation of serpentinite in mantle wedges requires an abundant supply of fluids from the subducting plate or possibly from repeated serpentinite dehydration (e.g., Hyndman and Peacock 2003).…”
Section: Interpretation Of the Resistivity Modelmentioning
confidence: 93%
“…At the junction of the Southwest Japan arc and Ryukyu arc, subduction of the Philippine Sea plate with fluid-rich materials introduced large volumes of fluids into the active arc system, leading to voluminous volcanism and a locally extensional stress regime (Aizawa et al, 2021;Mahony et al, 2011). As a result, in the Aso volcanic region, four large caldera-forming eruptions (Aso-1-Aso-4) occurred from ∼300 to ∼87 ka, and the large caldera was formed by losing large amounts of magma beneath the volcanic region.…”
Section: A Large Cumulative Normal Faulting Displacement On the Currently Dextral Strike-slip Futagawa Faultmentioning
confidence: 99%